Genetic relationships of salep orchid species and gene flow among Serapias vomeracea × Anacamptis morio hybrids - Palaz, Esra Bulunuz; Demirel, Fatih; Adali, Sümeyye; Demirel, Serap; Yilmaz, Abdurrahim (Plant biotechnology reports, 2023)
Orchids are naturally grown in many countries of the Eastern Mediterranean. Salep, produced from orchid tubers via grinding and used as a hot drink, is an essential ingredient of ice cream. Salep orchid species are in danger of extinction due to the absence of cultivation and over-harvesting from nature. In this study, the genetic diversity and population structure between salep orchid species, their hybrids, and commercial species of Phalenopsis sp. were first investigated using inter-Primer Binding Site (iPBS) Retrotransposon markers. A total of 854 bands were scored with a 100% polymorphism rate. Neighbor-joining, model-based structure, and PCoA (Principal Coordinate Analysis) algorithms clustered the 30 salep orchids into three main populations. The analysis of molecular variance revealed variations within and among the populations as 71% and 29%, respectively. Anacamptis morio and Serapias vomeracea had the furthest genetic distances, and F 1 hybrids of S. vomeracea and A. morio had great genetic diversity. The study results will provide helpful information for orchid breeding by eliciting the genetic distances of salep orchids.